Compartmentalized β1-adrenergic signalling synchronizes excitation–contraction coupling without modulating individual Ca2+ sparks in healthy and hypertrophied cardiomyocytes. Issue 13 (7th February 2020) - Yang, Hua-Qian; Zhou, Peng; Wang, Li-Peng; Zhao, Yan-Ting; Ren, Yu-Jie; Guo, Yun-Bo; Xu, Ming; Wang, Shi-Qiang
Abstract: Aims: β-adrenergic receptors (βARs) play pivotal roles in regulating cardiac excitation–contraction (E-C) coupling. Global signalling of β1 ARs up-regulates both the influx of Ca 2+ through sarcolemmal L-type Ca 2+ channels (LCCs) and the release of Ca 2+ from the sarcoplasmic reticulum (SR) through the ryanodine receptors (RyRs). However, we recently found that β2 AR stimulation meditates 'offside compartmentalization', confining β1 AR signalling into subsarcolemmal nanodomains without reaching SR proteins. In the present study, we aim to investigate the new question, whether and how compartmentalized β1 AR signalling regulates cardiac E-C coupling. Methods and results: By combining confocal Ca 2+ imaging and patch-clamp techniques, we investigated the effects of compartmentalized βAR signalling on E-C coupling at both cellular and molecular levels. We found that simultaneous activation of β2 and β1 ARs, in contrast to global signalling of β1 ARs, modulated neither the amplitude and spatiotemporal properties of Ca 2+ sparks nor the kinetics of the RyR response to LCC Ca 2+ sparklets. Nevertheless, by up-regulating LCC current, compartmentalized β1 AR signalling synchronized RyR Ca 2+ release and increased the functional reserve (stability margin) of E-C coupling. In circumstances of briefer excitation durations or lower RyR responsivity, compartmentalized βAR signalling, by increasing the intensity of Ca 2+ triggers, helped stabilize the performance of E-C coupling and enhanced the Ca 2+ transient amplitude in failing heart cells. Conclusion: Given that compartmentalized βAR signalling can be induced by stress-associated levels of catecholamines, our results revealed an important, yet unappreciated, heart regulation mechanism that is autoadaptive to varied stress conditions.